Two species of the genus Acanthaspis amyot et serville, 1843 (Heteroptera: Reduviidae: Reduviinae) newly recorded from Vietnam - Lam, Truong Xuan (Academia Journal of Biology, 2014)
The big-sized genus Acanthaspis Amyot et Serville, 1843 (Reduviidae: Reduviinae) is diverse in the tropical areas of African and Oriental Regions. About 110 species have been known in the world (Amyot & Serville, 1843, Amyot & Serville, 1843, Amyot & Serville, 1843, Hsiao, 1976, Maldonado Capriles, 1990). In the fauna of Vietnam so far only 2 species A. ruficep Hsiao and A. quinquespinosa (Fabricius) of genus Acanthaspis have been recorded (Dang Duc Khuong, 2007), in this present paper two species Acanthaspis geniculata Hsiao, 1976 (fig. 1 a h) and Acanthaspis subnermis Hsiao, 1976 (fig. 2 a h) of the genus Acanthaspis belong to subfamily Reduviinae are newly recorded and describle for the fauna of Vietnam. This reseach is supported by Natural Science Foundation of Vietnam (No. 6.021.06).